Is there an export‐ or import‐led growth in emerging countries? A case of BRICS countries. Issue 3 (23rd January 2020) - Raghutla, Chandrashekar; Chittedi, Krishna Reddy
Abstract : The BRICS economies could be considered a world number one trading group in one respect and emerging economies in another. The study applied both Johansen cointegration methodology for the long‐run relationship and Granger causality test for the direction of causality for the period of 1979–2018. The study findings confirmed that the growth‐led exports (GLE) hypothesis model is relevant for India, South Africa, and China, while exports‐led growth (ELG) hypothesis model is relevant for both Brazil and Russia. The growth‐led imports (GLI) hypothesis model is relevant for Brazil, India, China, and South Africa, while import‐led growth (ILG) hypothesis model is relevant for Russia. Hence, based on the findings, we confirmed that trade‐led growth hypothesis is valid. Finally, the results show that domestic and global demand contributes to a larger trade; countries that are labor‐abundant generate employment and foster economic growth.